Learn & Fun Chinese Class Sebagai Sistem Pengajaran Ilmu Mandarin yang Efektif dan Efisien - Heru Wijayanto Aripradono; David Febrian (Cattleya Darmaya Fortuna, 2024)
Currently, in Indonesia and several other countries, Mandarin is the second international language after English. This is because China's economy is growing rapidly. Apart from the economic perspective, China is also a source of investment from various countries, one of which is Indonesia. The aim of this research is to create more innovative, relevant and effective solutions. This research updates the game method